2006
DOI: 10.2133/dmpk.21.19
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Induction of Cytochrome P450 by NO-1886 (Ibrolipim), a Lipoprotein Lipase-Promoting Agent, in Primary Cultures of Human Hepatocytes and in Female Rat Liver

Abstract: The mRNA levels of human cytochrome P450 (CYP)2Cs and CYP3As in primary cultures of freshly isolated human hepatocytes were assessed after exposure to NO-1886 and rifampicin, a typical inducer of CYP3As. mRNA levels were analyzed by real-time RT-PCR using an ABI PRISM 7700 Sequence Detector system. Exposure to NO-1886 for 24 hr at a concentration of less than 10 microM showed only a tendency to reduce or increase the expression levels of CYP2C8, CYP2C9, CYP2C19, CYP3A4, or CYP3A5 mRNA. A higher concentration (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Table 5 lists the references for our studies concerning the measurement of these human mRNA targets by the TaqMan method. We have adopted the one-step RT-PCR method to measure the expression levels of every target gene related to the gene induction of drug-metabolizing enzymes in primary cultures of human hepatocytes 59,61,65,[67][68][69][70][71] and to the tissue-specific profiles of mRNA expression in human tissues, as described in our previous studies 9, [12][13][14]60,72) and the present study.…”
Section: Resultsmentioning
confidence: 99%
“…Table 5 lists the references for our studies concerning the measurement of these human mRNA targets by the TaqMan method. We have adopted the one-step RT-PCR method to measure the expression levels of every target gene related to the gene induction of drug-metabolizing enzymes in primary cultures of human hepatocytes 59,61,65,[67][68][69][70][71] and to the tissue-specific profiles of mRNA expression in human tissues, as described in our previous studies 9, [12][13][14]60,72) and the present study.…”
Section: Resultsmentioning
confidence: 99%
“…10) Moreover, we confirmed that the induction of drug-metabolizing enzyme and transporter mRNAs could be evaluated after 24 h of exposure to these inducers. 4,12,20) The changes in CYP1A2 mRNA levels induced by exposure to Ome in primary cultures of cryopreserved human hepatocytes using traditional and micro-space plates are shown in Figure 7. On the traditional plate cultures, the level of CYP1A2 mRNA in hepatocytes from Lots 100, LMP and VUA increased by 74-, 25-and 101-fold, respectively, after exposure to 50 mM Ome compared with that in 0.1% DMSO-treated controls, while on micro-space plate cultures, the level increased by 34-, 32-and 41-fold, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…22) We previously found that after exposure to 50 mM NO-1886 in primary cultures of freshly isolated and cryopreserved human hepatocytes, the level of CYP3A4 mRNA significantly increased by about 2-to 3.6-fold, while that of CYP1A2 increased by 2-fold or less, compared to the 0.1% DMSO-treated controls. 23,24) We evaluated the levels of gene expression of CYP1A2 and CYP3A4 in primary cultures of cryopreserved human hepatocytes after exposure to eight NO-1886 derivatives (A, B, C, D, E, F, G and H) (Figs. 3 and 4).…”
Section: Resultsmentioning
confidence: 99%